Phylogenetic analysis of the millipede genus Argentocricus Verhoeff, 1941 (Spirobolida, Rhinocricidae) based on morphological characters - Elesbão Silva Rodrigues, Patrícia; Campos, Luiz Alexandre; Valiati, Victor Hugo; Domingos Brescovit, Antonio; Lopes Rodrigues, Everton Nei [UNESP] (Taylor & Francis, 2024)
This paper offers the first cladistic analysis of the genus Argentocricus Verhoeff, 1941 based on the most comprehensive morphological data matrix focusing on Rhinocricidae to date. We evaluated 50 morphological characters for 40 species as terminal taxa, representing all the nine species of Argentocricus and 31 outgroups. We performed a parsimony analysis under Implied Weighting (IW), obtaining one most parsimonious tree (K = 8.274, fit = 4.680). We obtained a monophyletic Argentocricus including two species of Rhinocricus supported by the following synapomorphies: sternite of anterior gonopod with median portion and very evident coxite; telopodite of anterior gonopod in posterior view with a membranous bulge; and external branch of the posterior gonopod digitiform. Expanded coxae of the male leg pairs 3, a character traditionally used to diagnose the genus, was not recovered as a synapomorphy. Based on the resulting topology, we propose transferring Rhinocricus boggianii Silvestri, 1898 and R. venefica Chamberlin, 1947 to Argentocricus resulting in a new combination of Argentocricus boggianii (Silvestri, 1898) comb. nov. and Argentocricus veneficacomb. nov. In addition, a new diagnosis for the genus and a distribution map for all species are provided. We propose new characters potentially useful for future phylogenetic studies.
Keywords: millipedes; Myriapoda; neotropical region; phylogeny